Cursinhos preparatórios para residência médica: reflexões sobre possíveis causas e consequências - Hamamoto Filho, Pedro Tadao [UNESP] (2011)
Brazilian higher education has undergone significant changes in recent years, following the university reform and the expansion of the private sector. There are a growing number of medical schools, yet the number of medical residency places has not increased accordingly. The stiff competition for residency places can lead students to seek study support, such as preparatory courses. The presence of students in these courses can have a negative influence on the learning methods of trainee doctors, as the latter are subjected to restrictive study routines and standards. Understanding these courses as a reflection of the imbalance of health and education policies, there is an identifiable need for health education policies based on social needs.